DRUG ABUSER PERSONALITY REFLECTED IN BEV’S CHARACTER IN HOWARD’S MOVIE HILLBILLY ELEGY (2020) - Nurul Ayu Maya Shofia (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2022)
This study is aimed to analyze Drug Abuser Personality Reflected In Bev’s Character In Howard’s Movie “Hillbilly Elegy (2020)”. There are two problem statements in this research. The first is how is the personality of Bev before using drugs in Howard's movie? and second is how the personality of Bev after using drugs in Howard's movie “Hillbilly Elegy”. The study uses descriptive qualitative method to analyzed the film entitle “Hillbilly Elegy” directed by Howard as the objective of the research. The method of collecting data includes watching and reading, identifying, classifying, and selecting. The method of analyzing the data by displaying, explaining, and interpreting. The data analyzed by using Abnormal psychology and Sigmund Freud Psychoanalysis. The results of the study shows that Hillbilly Elegy gives new hope that people with mental disability can live like other normal people after get addicted to drugs, there are two points from the result (1) Bev's psychological condition before using drugs as reflected in Howard's Hillbilly Elegy. (2) Bev's psychological condition after using drugs as reflected in Howard's Hillbilly Elegy such as generalized stress disorder anxiety disorder, and post-traumatic stress disorder.